Pengaruh Electronic Word Of Mouth (E-Wom) Dan Celebrity Endorsement Terhadap Minat Beli Konsumen: Studi Pada E-Commerce Zalora dengan Brand Image Sebagai Variabel Mediasi - Handika Wisnu Wardhana; Zakaria Wahab; Muchsin Saggaff Shihab; Yuliani Yuliani (Coopetition : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine and analyze the effect of electronic word of mouth (e-wom) and celebrity endorsement on consumer buying interest in Zalora e-commerce with brand image as a mediating variable. This research includes explanatory research. The population in this study are people in Palembang City who have never shopped at Zalora e-commerce. The number of research respondents was set at 230 respondents and the data collection technique used the Probability Sampling technique. The sample criteria in this study are people in Palembang City who have never shopped at Zalora e-commerce. The results obtained indicate that based on the research results show that celebrity endorsement has no effect on people's buying interest in Zalora e-commerce, Electronic Word of Mouth (E-WoM) variable affects the brand image of Zalora products, Brand image variable affects consumer buying interest Zalora product, Variable Electronic Word of Mouth (E-WoM) affects Purchase Interest with Brand Image as Mediation, Celebrity Endorsement Variable on Purchase Interest with Brand Image as Mediation.